Virtual Learning Environment (VLE) as a didactic tool for Content and Language Integrated Learning (CLIL) in Sociology of Education - Manuel Roblizo Colmenero; Ramón Cózar Gutiérrez (Universitat Politècnica de València, 2018)
In the teaching practice based on Content and Language Integrated Learning (CLIL) some communication difficulties arise due both to lecturers' and students' differing linguistic skills and the complexity of matter-specific jargon. We present an experience of everyday use of the virtual learning environment (VLE) as a facilitating tool in the teaching of Sociology of Education for would-be Primary Education teachers, using English as vehicle language in a Spanish-speaking country. To this end, we use the results of surveys carried out with students enrolled in the same subject and center in two different academic years. Whereas in one of the groups the teaching was developed through a virtual learning environment (VLE)-based manner, in the second group teaching was only complementarily supported by virtual environments. We notice how students assigned a better value to Content and Language Integrated Learning (CLIL) teaching in the first aforementioned methodology, which allowed them to perceive the use of English as a vehicle language as less problematic -with the potential improvement in its practice that is implicit throughout the process. Thus, we found that virtual learning environment serves as a means for implementation of an active teacher training that efficiently combines the learning of Sociology of Education with the practice of a second language. Additionally, it has been observed that VLE-based methodology facilitates the implementation of cooperative, active and inductive teaching practices when it comes to the use of a language different from the mother tongue.